AB1143 Successful control of churg-strauss syndrome with omalizumab. (23rd January 2014) - Iglesias, E.; Camacho, M.; Delgado, I.; Lirola, M.J.; Bernabeu, J.; Neth, O.
Abstract : Background: Churg-Strauss syndrome (CSS) is extremely rare in children and is associated with higher cardiopulmonary disease and mortality rates compared to adult patients (1). Treatment consists essentially of corticosteroids (CST), however patients with severe or refractory disease might benefit from combination therapy with other immunosuppressive drugs. Omalizumab, an IgE blocking mAb has been recently used to decrease asthma activity in CSS patients (2). Objectives: We report the case of a 10-year-old girl with CSS who presented to us with vomits, abdominal pain, weight loss, paresthesias of lower extremities and breathlessness with a history of asthma, sinusitis and allergic rhinitis. Results: On examination she had skin nodules on her left side and 3rd and 4th proximal phalange of both hands and audible pericardial rub. Chest-x ray demonstrated cardiomegalia and echocardiogram showed pericardial effusion. Blood tests revealed eosinophilia (WBC 20.480; Eo 10.900/mm 3 ), ESR 59 mm/h and CRP 31.4 mg/L. Pulmonary HR-CT ruled out interstitial lung disease and adenopathies and performed bronchoscopy demonstrated 17.6% of eosinophils on BAL with negative cultures and/or stains for virus, fungus and acid-fast bacilli. Pulmonary function tests showed combined obstructive and restrictive disease and bone marrow aspirate confirmed central eosinophilia. Immunologic workup including IgGAM and E, ANA, ANCA and complement were normal apart from raised IgE levels (2169 kU/L; normal 0-20). Skin biopsy demonstrated necrotizing granulomatous inflammation with eosinophils and IgGAM and C3 deposits compatible with CSS. She commenced metylprednisolone (MP) bolus (30mg/kg/d) and monthly cyclophosphamide (CYP) (500-750 mg/m 2 ) with good clinical response. Clinical relapse occurred at 7 months presenting with vomits, a raised ESR (43 mm/h) and esophageal biopsy showed nonspecific intraepithelial inflammatory infiltrate. She remained CST dependent despite CYP suffering from gastrointestinal and respiratory symptoms. Rituximab (375 mg/m 2 /sem 4 weeks) followed by mycophenolate and immunoglobulin infusion could not control her disease. Subsequently, 2 years after initial clinical presentation omalizumab was started (150 mg sc/2 weeks) with good clinical response and CTS could be tapered to 5 mg/day whilst blood eosinophilia disappeared. Currently, 10 months after initiation of omalizumab, she has no gastrointestinal, neurological or cutaneous involvement whilst respiratory symptoms have markedly improved. Conclusions: Omalizumab might be a treatment option in the management of children suffering from this rare disease, allowing sparing CTS. A prospective international study is necessary to confirm this observation. References: Zwerina J, Eger G, Englbrecht M, et al. Churg-Strauss syndrome in childhood: A systematic review and clinical comparison with adult patients. Semin Arthritis Rheum 2009;39:108-115 Giavina-Bianchi P, Kalil J. Omalizumab administration in Churg-Strauss syndrome. Eur J Intern Med 2009;e139 Disclosure of Interest: None Declared